Theoretical and experimental progress of metal electrocatalysts for the nitrogen reduction reaction. (20th January 2023) - Zhang, Shishi; Zhang, Xiaoxue; Liu, Chengguang; Pan, Lun; Shi, Chengxiang; Zhang, Xiangwen; Huang, Zhen-Feng; Zou, Ji-Jun
Abstract : We reviewed the NRR performance of metal-based electrocatalysts with different sizes, further discussing the modulating strategies of highly efficient electrocatalysts. Abstract : Ammonia (NH3 ) has extensive applications in various fields and is mainly produced under high-temperature and high-pressure via the Haber–Bosch process, which leads to massive energy consumption. Electrocatalytic N2 reduction to NH3 is an attractive alternative for ammonia synthesis under ambient conditions. Inspired by N2 -fixation in biology, metal-based materials have been generally considered as promising nitrogen reduction reaction (NRR) electrocatalysts. The catalytic properties of metal species are significantly affected by their size due to the structure–reactivity correlations. In this review, we highlight theoretical and experimental studies on electrocatalytic N2 fixation with a focus on metal materials with different sizes (single atoms, metal nanoclusters, and metals and their alloy nanoparticles). The geometry structure and corresponding chemical properties will be discussed on the account of experimental and theoretical studies. Furthermore, we will summarize the modulation strategy of metal-based materials for optimized electrocatalytic performance in the NRR. By revealing the intrinsic connection between the electronic structure and the catalytic performance, we will provide a perspective on the future catalytic material design for the NRR.